2016
DOI: 10.1371/journal.pone.0155215
|View full text |Cite|
|
Sign up to set email alerts
|

Based on Molecular Profiling of Gene Expression, Palmoplantar Pustulosis and Palmoplantar Pustular Psoriasis Are Highly Related Diseases that Appear to Be Distinct from Psoriasis Vulgaris

Abstract: IntroductionThere is a controversy surrounding the existence of palmoplantar pustulosis (PPP) and palmoplantar pustular psoriasis (PPPP) as separate clinical entities or as variants of the same clinical entity. We used gene expression microarray to compare gene expression in PPP and PPPP.Methodology/Principal findingsSkin biopsies from subjects with PPP (3), PPPP (6), psoriasis vulgaris (10) and acral skin from normal subjects (7) were analyzed using gene expression microarray. Principal component analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…Histology staining confirmed the presence of intra-epidermal pustules (Figure 1A). In addition, we compared our PPP results with published transciptome profiles obtained from fresh tissues(6). The majority of genes altered in PPP (82% of PPP-increased genes and 76% of PPP-decreased genes) were confirmed by our study (see Figure E1 in the Online Repository).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histology staining confirmed the presence of intra-epidermal pustules (Figure 1A). In addition, we compared our PPP results with published transciptome profiles obtained from fresh tissues(6). The majority of genes altered in PPP (82% of PPP-increased genes and 76% of PPP-decreased genes) were confirmed by our study (see Figure E1 in the Online Repository).…”
Section: Resultsmentioning
confidence: 99%
“…The same mutations were detected in PPP and AGEP, leading to speculation that similar molecular alterations may underlie these disorders (4, 5). Interestingly, gene expression study on PPP provided evidence that select neural genes were increased, raising the possibility that unique pathways are activated in this disease(6). However, the molecular abnormalities associated with GPP, PPP and AGEP have not been systematically compared on a transcriptome-wide level, and common and/or distinct mechanisms driving these inflammatory conditions have thereby remained largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] These patients may have localized palmoplantar psoriasis [3][4][5] or generalized psoriasis in addition to the palms and soles. 6 The relationship between palmoplantar types and subtypes is an area of significant interest and research especially relating to genetic similarities and differences and therapeutic options. 5 Pure palmoplantar pustulosis is recognized as a subtype of palmoplantar psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…PPP can present by itself, or along with plaque psoriasis where it is considered Palmoplantar pustular psoriasis (PPPP) [1,2]. Genetic studies indicate that PPP may not be related to psoriasis, possibly accounting for their different responses to certain treatments, namely TNF-α antagonists [3].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies indicate that PPP may not be related to psoriasis, possibly accounting for their different responses to certain treatments, namely TNF-α antagonists [3]. Gene expression microarray analysis has shown that PPP and PPPP are not distinct clinical entities and differ from psoriasis based on increased expression of GPRIN1 and ADAM23 at the gene and protein level [2]. PPP is more common in middle-aged women, diabetics and smokers [1].…”
Section: Introductionmentioning
confidence: 99%